Conceptualizing Emergent States: A Strategy to Advance the Study of Group Dynamics. Issue 1 (1st January 2016) - Waller, Mary J.; Okhuysen, Gerardo A.; Saghafian, Marzieh
Abstract: In this review, we aim to advance work on group and team dynamics by examining how important elements of dynamism are embedded in the current literature on emergent states in groups. We use the concept of emergence as an organizing frame, building block, and critical lens, first summarizing key aspects of the extant literature on emergence, and then drawing four core characteristics of emergent phenomena from this literature. We use these characteristics to organize our review and examine how emergent states are portrayed in the past decade of groups literature. We end by exploring challenges to the development of a more dynamic perspective and by offering specific suggestions to guide and advance future work on groups and teams.